An adaptive back-stepping control for blood glucose regulation in type 1 diabetes. (April 2021) - Sepasi, Shiva; Kalat, Ali Akbarzadeh; Seyedabadi, Masoud
Highlights: A new adaptive back stepping control method has been suggested for regulating blood glucose in type 1 diabetics. Due to choose adaptive control scheme, it does not need parameters of model of blood glucose to be known. Convergence of blood glucose to its desired value is guaranteed by Lyapunov stability theory. Abstract: In this paper, an adaptive back-stepping controller is designed to regulate the blood glucose in type 1 diabetics. Bergman's minimal model (BMM) is employed to mathematically model Type 1 diabetes mellitus (T1DM). Firstly, an adaptive virtual controller is designed to bring back the blood glucose level to its safe range. Then, a second adaptive controller is designed to determine the insulin intake. Controller performance and asymptotic stability of the adaptive back-stepping method is proved using Lyapunov stability theory. To verify the effectiveness of the proposed approach in tracking the desired blood glucose, simulation results have been performed. Meal disturbance to diabetes patient is also definitely described and is presented in simulation results. The results show the advantages of the proposed controller such as proper convergence time, robustness in the presence of external disturbances and uncertainties in human body parameters.